ANALISIS PENURUNAN KUANTITAS SISWA MISKONSEPSI PADA KONSEP KINEMATIKA - Riski Muliyani; Yudi Kurniawan (Universitas Sriwijaya, 2021)
This study was aimed to provide a comprehensive description of the analysis of the decreasing the numbers of students that misconceptions in the kinematics concepts. This quantitative research used the one-group pretest-posttest design on the 2019/2020 academic year. The populations of this study were 482 students in senior high school (8th grade) in Singkawang City and 168 students who had participated as samples. The instrument that used in this study was designed as four tier-tests in multiple-choice form dan structured interview form. The results of this study show that has been decreasing in the number of students whose misconceptions throughout the sub-concepts of particle kinematics with 6 sub-concepts reached the medium category and only one sub-concept reached the low category. Based on this data, it suggested for that further researchers can optimize the implementation of learning models to reach the higher decreasing misconception categorize or zero points (0%) of misconception